2011
DOI: 10.1177/1934578x1100601227
|View full text |Cite
|
Sign up to set email alerts
|

Two New Phenolic Glycosides from Viburnum plicatum var. plicatum f. plicatum

Abstract: Two new glycosides, named dideoxyplicatumoside A (1) and erythro-syringylglycerol-β-O-4′-(+)-isoeucommin A 4′′′-O-β-D-glucopyranoside (2), together with seven known compounds, were isolated from the leaves of Viburnum plicatum Thunb. ex Murray var. plicatum f. plicatum. Their structures were established on the basis of NMR, MS and chemical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Among them, 4 was reported from Viburnum genus for the first time; 3 was also reported from V. awabuki [13] and V. plicatum var. plicatum f. plicatum [14], 7 from V. punctatum [15], 8 from V. tinus [16], and 9 from V. dilatatum [17] and V. erosum [18].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 4 was reported from Viburnum genus for the first time; 3 was also reported from V. awabuki [13] and V. plicatum var. plicatum f. plicatum [14], 7 from V. punctatum [15], 8 from V. tinus [16], and 9 from V. dilatatum [17] and V. erosum [18].…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C NMR spectrum of 1 showed 30 carbon signals, of which δ C 147.3, 119.2, 115.6, 111.0, 70.6, and 56.1 were overlapping signals. The 1 H and 13 C NMR ( Table 1 and Table 2 ) indicated a furofuran lignan glycoside for 1 , which shared high similarity with those of erythro -syringylglycerol- β - O -4′-(+)-isoeucommin A 4‴- O - β -D-glucopyranoside [ 9 ], except for the different substitution of aryl groups with the C-4/C-5″replaced by hydrogen and C-5/C-3″ replaced by hydroxyl. The location of the substitution of aryl groups of 1 wasfurther determined by HMBC spectroscopic analysis ( Figure 2 ).The small coupling constants of J H-7, H-8 (4.1Hz)/ J H-7′, H-8′ (4.0 Hz) and the chemical shift differences of Δ δ H–9 (0.4) and Δ δ H–9′ (0.4) (Δ δ H–9 = δ H–9a – δ H–9b andΔ δ H–9′ = δ H–9′a – δ H–9′b ) showed that the relative configuration was erythro [ 10 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…From V. plicatum var. plicatum f. plicatum , neolignans 214 , 217 and 226 were found [59] . Compounds 218 and 219 were purified from V. foetidum var.…”
Section: Chemical Constituents and Biological Activitiesmentioning
confidence: 99%
“…Lignans 246 – 268 containing the furofuran moiety were found in different Viburnum species ( Table 8, Figure 8). [9,50,56,59,63,64] Syringaresinol ( 252 ) and pinoresinol ( 253 ) from V. erosum exhibited considerable neuroprotective effects with EC 50 values of 6.33 and 6.96 μM by inhibiting the cell death of glutamate‐induced HT22 cells, as well as anti‐inflammatory activities with IC 50 values of 8.30 and 7.89 μM inhibiting NO production in LPS‐induced macrophage RAW 264.7 cells [56] . Compounds 254 , 255 , 266 and 267 displaying varying anti‐ α ‐glucosidase activity were obtained from the stems of Viburnum melanocarpum , among which, compound 267 showed stronger α ‐glucosidase inhibitory activity (IC 50 =10.3 μM) than the positive control acarbose (IC 50 =16.9 μM).…”
Section: Chemical Constituents and Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation